Paraquat poisoning from accidental ingestion leading to fatal outcome: A case report - Chao Liu; Mengya Yao; Jiangrong Ma; Shinan Nie (Journal of Acute Disease)
Rationale: Paraquat, a highly toxic bipyridyl herbicide lacking a specific antidote, poses severe risks upon ingestion. However, the diagnosis of paraquat poisoning is complicated by its nonspecific initial symptoms, particularly when a detailed exposure history is not provided. Patient’s Concern: A 33-year-old man inadvertently ingested an unknown liquid and presented to medical services a day later with complaints of ongoing nausea, vomiting, and diarrhea. The assessment revealed elevated serum creatinine, signaling acute kidney injury, initially thought due to gastroenteritis and dehydration. Diagnosis: Acute renal insufficiency due to paraquat poisoning. Interventions: The treatment involved fluid resuscitation and antibiotics, but his decline led to intensive care unit transfer. Subsequent chest computed tomography scans indicated lung changes indicative of paraquat poisoning. A detailed history review and comprehensive blood and urine toxicology screens confirmed the diagnosis. Subsequently, aggressive interventions such as hemoperfusion and continuous renal replacement therapy were initiated, yet there was a further decline in respiratory function, necessitating mechanical ventilation. The prognosis was poor, and ultimately, the family chose to withdraw care. Outcomes: The patient succumbed to his illness. Lessons: This case underscores the importance of promptly and accurately diagnosing paraquat poisoning, as its vague early signs can lead to diagnostic delays, crucial due to the condition’s rapid progression. Alertness to paraquat poisoning is essential in patients with sudden gastrointestinal and renal symptoms post-exposure. Additionally, it underscores the necessity for public health measures to avert paraquat ingestion and advance therapeutic approaches.